Latihan Kecepatan-Kekuatan dan Dampaknya terhadap Pengembangan Kekuatan Spesifik Kecepatan pada Lengan dan Kaki, serta Performa Servis Overhand dan Keterampilan Blocking dalam Bola Voli - Ali Hameed Ali AlZubaidi (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aimed to identify and design speed-strength exercises that develop speed-strength in the arms and legs of the research sample, and to enhance the skill performance of the tennis overhand serve and blocking in volleyball. Materials and Methods. The researcher employed an experimental design with pre- and post-tests, applying a training program consisting of 24 units over 8 weeks. The sample included 12 first-grade middle school players. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS). Results. The speed-strength exercises significantly improved arm and leg speed-strength among the participants. Additionally, the exercises had a positive effect on the accuracy of the overhand serve in tennis and blocking skills in volleyball. Conclusions. Speed-strength exercises are effective for enhancing both physical capabilities and technical performance, particularly for the overhand serve and blocking skills. It is recommended that coaches integrate such exercises into training programs to develop speed-strength as a core component of athletic performance.